Makna Dalam Film Iklan - Arif Agung Suwasono (Institut Seni Indonesia Yogyakarta, 2014)
Abstract. Film, is a medium in communication, but the logic-signs in the film is unique. It have more visibleand natural, and took away the coding message in communication. The power of film language is the signthat delivered, with visual icons and kinetic representation. Associated with commercial ad film, thearbitrary does not lie in the signs visually stunning, but on the meaning an associative obtained from themeanings sign coding ethnicity are semantically. What is served in the film ad is logic image of acommodities that delivered with a story that is frequently arbitrary, as a consequence of the ways in whichadvertise.Keywords: Film, Visual Representation, Advertising.